2002
DOI: 10.1124/dmd.30.9.970
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Specificity of CYP2D Isoforms in Rat and Human

Abstract: ABSTRACT:In rats, six cytochrome P450 (P450) 2D isoforms have been genetically identified. Nonetheless, there is little evidence of catalytic properties of each CYP2D isoform. In this study, using recombinant CYP2D isoforms (rat CYP2D1, CYP2D2, CYP2D3, and CYP2D4 and human CYP2D6) or hepatic microsomes, we investigated the catalytic specificity toward bufuralol, debrisoquine, and propranolol, which are frequently used as CYP2D substrates. Bufuralol was oxidized to three metabolites by rat and human hepatic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 27 publications
(25 reference statements)
4
41
0
Order By: Relevance
“…To date, there is little information about the catalytic specificity of CYP2D isoforms, especially CYP2D3 (Chow et al, 1999;Hiroi et al, 2002). In this study, we demonstrated that CYP2D3 was involving in diazepam p-hydroxylation in rats.…”
Section: Role Of Cyp2d3 In Polymorphism Of Diazepam P-hydroxylationsupporting
confidence: 48%
See 1 more Smart Citation
“…To date, there is little information about the catalytic specificity of CYP2D isoforms, especially CYP2D3 (Chow et al, 1999;Hiroi et al, 2002). In this study, we demonstrated that CYP2D3 was involving in diazepam p-hydroxylation in rats.…”
Section: Role Of Cyp2d3 In Polymorphism Of Diazepam P-hydroxylationsupporting
confidence: 48%
“…In addition, antibodies generated against the purified P450 enzymes are often not specific. Despite the structural similarities among CYP2D isoforms, significant differences in the ability to metabolize drugs have been observed among these CYP2D isoforms (Wan et al, 1997;Chow et al, 1999;Hiroi et al, 2002). In this study, we identified the enzyme involved in diazepam p-hydroxylation to be CYP2D3 using yeast recombinant CYP2D isoforms.…”
mentioning
confidence: 96%
“…Phe-483 is also notably absent in these orthologues. 2D4 is essentially inactive toward debrisoquine, although metabolism by 2D2 can proceed smoothly (71). Venhorst et al (21) have attributed this difference in 2D2/4/6 metabolism to a large negative electrostatic potential in the cavities of 2D2 and 2D6, which is quite different in 2D4.…”
Section: Resultsmentioning
confidence: 99%
“…Of the four rat CYP2D isoforms, substrate specificity (Wan et al, 1997;Hiroi et al, 2002;Grobe et al, 2012), region-selective metabolism (Suzuki et al, 1992;Masubuchi et al, 1993Masubuchi et al, , 1994Narimatsu et al, 1994), and a study on ligand-binding specificities by homology modeling (Venhorst et al, 2003) suggested that CYP2D2 functionally conserves human CYP2D6, and the markedly lower expression of CYP2D2 in female Dark Agouti rats than in Wistar and SD rats allowed female Dark Agouti rats to be used as a model of the CYP2D6 poor metabolizer phenotype in humans (Yamamoto et al, 1998;Schulz-Utermoehl et al, 1999). Homology modeling of rat and human CYP2D isoforms indicated that the negative electrostatic potential on the active site surface conferred common characteristics on both CYP2D2 and CYP2D6, which was distinct from the neutral electrostatic potentials calculated for the other rat CYP2D isoforms (Venhorst et al, 2003).…”
Section: Discussionmentioning
confidence: 99%